2005
DOI: 10.2214/ajr.184.6.01841836
|View full text |Cite
|
Sign up to set email alerts
|

CT Colonography After Fecal Tagging with a Reduced Cathartic Cleansing and a Reduced Volume of Barium

Abstract: In the present study, CT colonography after fecal tagging with 50 mL of barium combined with a reduced cathartic cleansing was feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
4
4

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 10 publications
3
54
4
4
Order By: Relevance
“…Likewise, the optimal timing and volumes of these agents remains to be optimised. Some authors have concluded that barium preferentially tags solid faecal material, leaving appreciable volumes of colonic fluid untagged [18]. Larger volumes of administered barium seem to tag a greater proportion of colonic fluid, but with layering [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the optimal timing and volumes of these agents remains to be optimised. Some authors have concluded that barium preferentially tags solid faecal material, leaving appreciable volumes of colonic fluid untagged [18]. Larger volumes of administered barium seem to tag a greater proportion of colonic fluid, but with layering [19].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors believe that barium predominately tags the more solid elements of the retained colonic residue [18]. Hyperosmolar iodine-based contrast agents promote stool softening by inducing colonic fluid secretion.…”
mentioning
confidence: 99%
“…Research into noncathartic approaches to minimize the bowel preparation is underway, but this technique has not yet been validated in a multicenter screening trial. [159][160][161] However, under conditions where same-day or next-day referral for colonoscopy would be possible, one drawback of noncathartic CTC is that a cathartic bowel preparation would still be required prior to removal of polyps.…”
Section: Ctcmentioning
confidence: 99%
“…One could argue that tagging effectiveness actually should be vice versa, exhibiting better results in the more proximal bowel segments,because the tagging agent might not have reached distal bowel parts in patients with decreased transit times. However, Lefere et al (30) reported similar observations …”
Section: Discussionmentioning
confidence: 78%